The implications of living with heart failure; the impact on everyday life, family support, co-morbidities and access to healthcare: a secondary qualitative analysis - Mirella Fry; Sarah McLachlan; Sarah Purdy; Tom Sanders; Umesh Kadam; Carolyn Chew‐Graham (2016)
The aim of this study was to use secondary analysis to interrogate a qualitative data set to explore the experiences of patients living with heart failure. The data-set comprised interviews with 11 patients who had participated in an ethnographic study of heart failure focusing on unplanned hospital admissions. Following an initial review of the literature, a framework was developed with which to interrogate the data-set. This was modified in light of analysis of the first two interviews, to focus on the rich data around patients’ perceptions of living with heart failure, managing co-morbidities, accessing healthcare and the role of their family and friends, during their illness journey. Respondents described how the symptoms of heart failure impacted on their daily lives and how disruption of routine activity due to their symptoms caused them to seek medical care. Respondents disclosed the difficulties of living with other illnesses, in addition to their heart failure, particularly managing multiple and complex medication regimes and negotiating multiple appointments; all expressed a desire to return to their pre-morbid, more independent lives. Many respondents described uncertainty around diagnosis and delays in communication from their healthcare providers. The importance of family support was emphasised, but respondents worried about burdening relatives with their illness. Living with heart failure causes disruption to the lives of sufferers. Facilitation of access to healthcare, through good communication between services and having a strong support network of both family and clinicians can reduce the impact of heart failure on the lives of the patient and those around them.